2022
DOI: 10.3390/su142316298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Perception and Experience of Rural Natural Landscape among Youth Groups: An Empirical Analysis from Three Villages around Hefei

Abstract: Research on the perception and evaluation degree that the rural natural landscape plays an important role in improving rural sustainable development and construction. However, the views of young people, who play a key role in social development, on the natural landscape of the countryside have been neglected. Based on the perspective of the rural natural landscape in China, this study combines the field research of Ma Ying, San Shi Gang, and Shen Fu villages around Hefei, Anhui Province, and constructs a perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The reliability analysis was obtained by calculating Cronbach's alpha, with a result of 93%. When the Cronbach's α value is higher than 70%, it indicates that the data are acceptable and reliable [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…The reliability analysis was obtained by calculating Cronbach's alpha, with a result of 93%. When the Cronbach's α value is higher than 70%, it indicates that the data are acceptable and reliable [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…The entropy-TOPSIS method first calculates the weights of indicators and then applies TOPSIS to determine the forest ecological safety index. The entropy weighting method [45] is a mathematical method that considers what each indicator conveys, objectively assigns weights to each indicator, and calculates a comprehensive index. The method uses entropy to calculate the weight values based on the information provided by each evaluation index value to overcome some drawbacks.…”
Section: Methodsmentioning
confidence: 99%
“…According to Jamal-e-Din Mahdi Nejad [21], rural landscapes' aesthetics, readability, clarity, and reading environment were extremely important, and their perception was also much influenced by symbols, landscapes, and shapes in the subjective index. Yanlong Guo [22] assessed the four aspects of rural landscape design-rural landscape ecology, water environment, climate, and sound. He concluded that the most important factors influencing adolescents' perceptions and experiences of the countryside were sound comfort, air cleanliness, and landscape adaptability.…”
Section: Synthesis Of Relevant Studiesmentioning
confidence: 99%